The Hero as Seer: Character, Perception and Cultural Health in Carlyle - Budge, Gavin (Romanticism and Victorianism on the Net, 2008)
AbstractA rhetoric of spectrality pervades Thomas Carlyle’s writings, in a way which is intimately related to his characteristic position of “natural supernaturalism.” This essay argues that Carlyle’s rhetorical emphasis on spectral hallucinations in his descriptions of social upheavals such as those of revolutionary France reflects the influence on his work of physiological theories of perception stemming from the medical thought of Erasmus Darwin, theories which are frequently invoked in early nineteenth-century theories of ghosts and apparitions. Carlyle’s preoccupation in his historical writing with the figure of the “Great Man” also reflects this medical context, in that the Great Man’s superior ability to perceive the reality of his historical moment is understood by Carlyle as indicative of a superior cultural “health” that he manages to convey to the society of his time, contrasted by Carlyle with the state of feverish delirium characteristic of revolutionary situations. The essay suggests that this relationship to theories of perception aligns the Carlylean “Great Man” to the figures of the Wordsworthian poet and the Romantic genius more generally, and also helps to explain the Victorian emphasis on “character,” of which the Carlylean historiography of “Great Men” is an example. The placing of individual character at the centre of accounts of perception by nineteenth-century thinkers such as Carlyle and Ruskin reacts against the determinism associated with Enlightenment thought’s assumption that in perception the mind is passively imprinted with sense-data, and reflects the influence of the alternative account of perception as a process of interpretation of signs put forward by Thomas Reid and other Common Sense philosophers.